Sistem Informasi Pendukung Keputusan Pemilihan Supplier Terbaik Menggunakan Metode Simple Additive Weighting (SAW) - Layla Nadira Romadhona dan Ali Mulyanto (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
Sinergi Multi Talenta Inc is a supplier company engaged in Cutting Tools & General, where Sinergi Multi Talenta Inc supplies the technical tools needed in the manufacturing industry. To meet the needs of partners or customers, Sinergi Multi Talenta Inc does not produce its own goods but buys goods from other suppliers or suppliers. Sinergi Multi Talenta Inc has customers, partners, and customers from large companies where the need for cutting tools & general is needed everyday and in large quantities. The quality of the goods, the price, and the time of delivery of the goods are taken into account so that the company can continue to run. Sinergi Multi Talenta Inc has problems in determining suppliers who can continue to be suppliers for customer needs, where the problem is high prices, long delivery of goods, payment due or cash, and quality of goods sold. The Best Supplier Decision Support System was made using the Simple Additive Weighting Method to help Sinergi Multi Talenta Inc decides the best supplier to continue working together. This system is designed with Boostrap Framework, Xampp. This system was developed using the PHP programming language and Codelgniter Framework with Bootstrap template, as well as MySql as the database management system.